Visible Light‐Induced Decarboxylative Alkylation of Heterocyclic Aromatics with Carboxylic Acids via Anthocyanin as a Photocatalyst. Issue 13 (27th May 2020) - Guo, Rui; Zuo, Minghui; Tian, Qinye; Hou, Chuanfu; Sun, Shouneng; Guo, Weihao; Wu, Hongfeng; Chu, Wenyi; Sun, Zhizhong
Abstract: A visible light‐induced decarboxylative alkylation of heterocyclic aromatics with aliphatic carboxylic acids was developed by using anthocyanins as a photocatalyst under mild conditions. A series of alkylated heterocyclic compounds were obtained in moderate to good yields by using the metal‐free decarboxylative coupling reaction under blue light. This strategy uses cheap and readily available carboxylic acids as alkylation reagents with good functional group tolerance and environmental friendliness. It is worth noting that this is the first time that anthocyanin has been used to catalyze the Minisci‐type C−H alkylation. The mechanism of decarboxylation alkylation was studied by capturing the adduct of alkyl radical and hydroquinone, thus confirming a radical mechanism. This protocol provides an alternative visible light‐induced decarboxylative alkylation for the functionalization of heterocyclic aromatics. Abstract : A visible light‐induceed decarboxylation alkylation of heterocyclic compounds with aliphatic carboxylic acids has been developed. Anthocyanin was used as photocatalyst for the first time in a type of decarboxylation reaction. This approach overcomes the traditional method that requires the use of a metal catalyst or other expensive complex catalysts with complicated synthesis steps. Finally, a series of control experiments verify the reaction path and reaction mechanism.